2012
DOI: 10.1002/ajmg.b.32061
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety symptoms among women who carry the FMR1 premutation: Impact of raising a child with fragile X syndrome is moderated by CRHR1 polymorphisms

Abstract: The fragile X mental retardation gene, FMR1, contains a polymorphic CGG repeat in the 5′-untranslated region of exon 1. Once unstable, this repeat is capable of expansion across generations. Women who carry a premutation allele (55–199 repeats) are at risk of passing on a full mutation allele (>200 repeats) to their offspring. A full mutation leads to the most common form of inherited intellectual disability, fragile X syndrome (FXS). Mounting evidence suggests that premutation carriers may be vulnerable to sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 54 publications
2
35
0
Order By: Relevance
“…Because we did not have activation ratio data, one X chromosome was selected for analysis in the present study as follows. Although we considered alternative approaches [Kline et al, 2014; Gustin et al, 2015], we followed the approach of Hunter et al [2012]. We selected the longer allele in mothers who had one expanded (i.e., > 40 CGGs) allele and one normal allele (n = 218) and in the one case who had two expanded alleles.…”
Section: Methodsmentioning
confidence: 99%
“…Because we did not have activation ratio data, one X chromosome was selected for analysis in the present study as follows. Although we considered alternative approaches [Kline et al, 2014; Gustin et al, 2015], we followed the approach of Hunter et al [2012]. We selected the longer allele in mothers who had one expanded (i.e., > 40 CGGs) allele and one normal allele (n = 218) and in the one case who had two expanded alleles.…”
Section: Methodsmentioning
confidence: 99%
“…At least in part this may be the result of genetic variation (for example, CRHR1 polymorphisms and release of cortisol) moderating the stress of raising a child with FXS [75,76]. However, one recent study has shown that poorer inhibitory control and working memory are associated with elevated social anxiety, depression, and attention deficit hyperactivity disorder (predominantly inattentive symptoms) among women with the FMR1 premutation [37].…”
Section: Reviewmentioning
confidence: 99%
“…Anxiety in women with the premutation has been linked with environmental factors such as child problem behaviors [75], with the impact of the stress of raising a child with fragile X syndrome moderated by variation on CRHR1 , a gene involved in cortisol regulation [97]. Epigenetic changes associated with abnormal methylation have also been implicated, with one study showing that methylation of the CpG10-12 sites located at the FMR1 intron 1 boundary predicted social anxiety with 92% sensitivity in women with the FMR1 premutation [98].…”
Section: Introductionmentioning
confidence: 99%